عقوبة الإعدام في القانون الليبي والشريعة الإسلامية: Dealth Penalty in Libyan Law and Islamic Law - H Belkasem, Boufaris Salaheden (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
تهدف الدراسة إلى التعرف على مفهوم عقوبة الإعدام واستكشاف الحالات التي يجب الحكم فيها بالإعدام. وتكمن مشكلة الدراسة إلى استناد القانون الليبي في نصوصه إلى الشريعة الإسلامية. وتبرز أهمية الدراسة في تسليط الضوء على نصوص القانون الليبي والشريعة الإسلامية. وتتمحور أهداف الدراسة في تبيان مفهوم عقوبة الإعدام في القانون الليبي والشريعة الإسلامية وإيضاح الجرائم التي يستلزم فيها تطبيق عقوبة الإعدام في القانون الليبي والشريعة الإسلامية. واتبعت الدراسة المنهج الإستقرائي لإستقراء نصوص الشريعة الإسلامية والقانون الليبي. كما اتبعت المنهج التحليلي لتحليل نصوص القانون الليبي في تطبيق عقوبة الإعدام. ولقد توصلت الدراسة إلى العديد من النتائج من بينها أن الشريعة الإسلامية هي المصدر الرئيسي للتشريع. كما أن القانون الليبي لايمكنها أن تتخلى عن تطبيق عن تطبيق عقوبة الإعدام في نظامها العقابي. ولقد أوصت الدراسة بضرورة إعادة تبويب وتصنيف القانون الليبي بما يسمح من توضيح نصوص القانون الليبي في عقوبة الإعدام. Abstract The purpose of the study is to determine the idea of the death penalty and research of the cases where the death sentence might be regulated. The predicament of the research, the Libyan law is based on the Islamic Shariah law, so it relies on the information according to Shariah. So, it signified both the Libyan law and Islamic Shariah. The research also recognized the systematic procedure to analyze the topics of the Libyan law about the execution of the death penalty. The study resolved from the conclusions that the Shariah is the main source of authorization to legalize the death penalty in the Libyan regulatory system. The study also revealed that the death penalty in Libya is under penal law so there is no possibility to surrender once the death penalty is legalized by the court. So, the study recommends that the Libyan law is required to amend in regards to the death sentence.